Synthesis, Characterisation, and Corrosion Inhibition Performance of a β-Cyclodextrin/Melamine Supramolecular Complex on St20 Steel in Acidic Media - Berdimurodov, Elyor; Eliboev, Ilyos; Dagdag, Omar; Lal, Basant; Berisha, Avni; Rajabov, Yusufboy; Mamatov, Jaykhun; Wan Nik, W. B.; Kholikov, Abduvali; Akbarov, Khamdam (Journal of bio- and tribo-corrosion, 2024)
Corrosion poses major challenges in various industrial sectors such as oil and gas, chemicals, and infrastructure. Traditional corrosion inhibitors have limitations in terms of toxicity and environmental compatibility. Supramolecular complexes are promising as green corrosion inhibitors, as the interaction between host and guest molecules can be tailored for different application needs. This study investigates a β-cyclodextrin (β-CD)/melamine (ME) supramolecular complex. The synthesis of the complex is confirmed by Raman spectroscopy, 1 H NMR, and FT-IR methods. A range of characterisation techniques are used to analyse the complex’s structure. Gravimetric and electrochemical tests, including potentiodynamic polarisation and electrochemical impedance spectroscopy, evaluate its corrosion inhibition performance on steel in 0.5 M HCl solution at varying concentrations (25–100 mg/L) and temperatures (303 to 333 K). Computational modelling, including Density Functional Theory, Monte Carlo, and Molecular Dynamics simulations, provides atomic-scale insights into the mechanisms of inhibition. The synthesis, characterisation, and corrosion prevention performance of a novel supramolecular complex, β-cyclodextrin/melamine (β-CD/ME), on St20 steel, in acidic conditions, were the subjects of an inventive investigation that was described in this publication. The complex’s structural alterations, physical interactions, and structure were effectively disclosed, using Raman spectroscopy, 1 H NMR, and FT-IR. The β-CD/ME complex’s ability to prevent corrosion in hostile solutions exceeded 92–94%, resulting in the formation of a thin protective film on the metal surface and acting as a mixed-type inhibitor. A novel mix of theoretical and experimental methods is used in this work to comprehend the underlying mechanisms, including the influence of structural factors on corrosion prevention effectiveness and the adsorption energies of the complex on the metal surface. Electrochemical tests showed a significant increase in charge transfer resistance ( R ct ) and a decrease in corrosion current density ( i corr ), confirming the formation of a protective film. The adsorption energy of the complex on the metal surface was found to be − 461.85 kcal/mol, indicating strong interaction. These findings demonstrate that the β-CD/ME complex acts as a highly promising, cost-effective, eco-friendly, and efficient corrosion inhibitor with potential applications across diverse industrial settings.